Prospects for prevention of adhesion process during cardiac surgical interventions - M. G. Shurygin; I. A. Shurygina (Acta Biomedica Scientifica, 2021)
The article is devoted to the problem of prevention of adhesions in cardiac surgery. It was determined that the problem is urgent due to the increase in the number of heart surgeries. The formation of adhesions is a reaction of the body after surgery, which is a stage of healing and partly performs a protective function. Nevertheless, the presence of adhesions violates the mechanical properties of the heart, negatively affects central hemodynamics, complicates the surgeon’s task during repeated surgical interventions and increases the risk of repeated operations.It has been shown that at present, for the prevention of adhesions, researchers tend to use biodegradable barrier materials with biocompatibility and the ability to dissolve after performing the barrier function. The main anti-adhesion agents used in cardiac surgery are membranes and gels. The requirements for an “ideal” agent for the prevention of adhesion were determined: biocompatibility, no irritating effect, no effect on wound healing, suppression of the growth of connective tissue in the pericardium.Conclusions. Until now, none of the funds has all the necessary qualities to prevent adhesion in the pericardium. Therefore, the search for effective methods for the prevention of postoperative adhesions remains relevant for cardiac surgery.